TOXOLOGICAL AND PATHOLOGICAL STUDY OF DIAZINON ON MALE WILD PIGEON ( Culumba livia gaddi) IN BASRAH CITY - Majeed S. K (Basrah Journal of Veterinary Research)
A five months as toxologic pathologic study of diazinon on male wild pigeons ( Culumba livia gaddi) by oral intubation was done. The animals divided to four groups each with six pigeons: A( high dose 0.6 mg), B( intermediate dose of 0.3 mg), C( low dose 0.15 mg) and D(untreated control). Clinical observation of treated pigeons did not show significant changes, but a clear histopathological changes were founded. In livers of group A showed a periportal foci of mononuclear cells, while, another showed a septal fibrosis and foci of mononuclear cells in the same group. A foci of mononuclear cells were shown in group B. In group C there was a periportal fibrosis, congestion and foci of mononuclear cells. A dilated cortical tubules were showed in kidney in all groups. While, in section from sciatic nerve related to groups (A-C) showed degenerated and vacuolated nerve fibers, and vacuolated nerve fibers were founded in group B and C. A several degenerate vacuolated nerve fibers were founded in the spinal cord of pigeons in A group, while, in B group a degenerate, vacuolated nerve fibers. In C group a several degenerate, vacuolated nerve fibers